Nowe życie Orhana Pamuka i Jeśli zimową nocą podróżny Italo Calvino, czyli o książce w książce - Młynarczyk, Anna (Studia Azjatystyczne, 2015)
This article presents two aspects of showing the power of literature. Orhan Pamuk, a Turkish Nobel prize winner, in his book New life is more focused on the content of the novel. Main characters of the story are entirely devoted to one book that totally changes their lives. Italo Calvino is more focused on the structure. His characters take part in a great adventure just to find the end of the story that they are interested in. The main goal of this article is to show differences and similarities in showing the same literary issue. Italo Calvino's novel is more optimistic and positive. Literature has good influence on his characters. On the other side, Orhan Pamuk's novel shows a destructive side of literature. Characters in his book seem to be defeated from the very beginning. Those two books show in a very good way the difference between European optimism and Oriental, especially Turkish, sentimentality, which in Turkish language has its own name – hüzün. It can be translated as 'blues, sadness, spleen'. Both novels present the power of literature and its influence on readers.